Sarcoglaucins A-I, new antifouling cembrane-type diterpenes from the South China Sea soft coral Sarcophyton glaucum. Issue 12 (1st May 2019) - Zhang, Jing; Tang, Xuli; Han, Xiao; Feng, Danqing; Luo, Xiangchao; Ofwegen, Leen van; Li, Pinglin; Li, Guoqiang
Abstract : Nine new cembrane diterpenes, named sarcoglaucins A-I (1–9 ) along with three known analogues, trochelioid (10 ), 7α-hydroxy-Δ 8(19) -deepoxysarcophine (11 ), and (−)-sartrochine (12 ), were isolated from the soft coral Sarcophyton glaucum collected at Xisha Islands in the South China Sea. Abstract : Nine new cembrane diterpenes, named sarcoglaucins A-I (1–9 ) along with three known analogues, trochelioid (10 ), 7α-hydroxy-Δ 8(19) -deepoxysarcophine (11 ), and (−)-sartrochine (12 ), were isolated from the soft coral Sarcophyton glaucum collected at Xisha Islands in the South China Sea. The structures of all the compounds were established by extensive spectroscopic analysis. The absolute configurations of sarcoglaucins A and B with an unusual [10.3.2.1] cage-type structure were determined using X-ray diffraction and quantum chemical calculation methods. Sarcoglaucin B (2 ), sarcoglaucin E (5 ) and compounds10–12 showed strong antifouling activity against the barnacle Balanus amphitrite .